Living politics after war : ex-combatants and veterans coming home - Söderström, Johanna; Guittet, Emmanuel Pierre (Manchester : Manchester University Press, 2020)
Life after war is intrinsically political for former combatants. As wars end, societies and former combatants face a period of transition. This book explores the experience of coming home for former combatants, capturing the challenges and opportunities for political mobilization among former combatants as they return from three very different wars: South West Africa People's Organization combatants who participated in the Namibian War of Independence (1966-90); guerrillas from Movimiento 19 de Abril who joined the ongoing guerilla warfare conducted against the Colombian state (1974-90), and combatants from the United States who participated in the Vietnam War (1955-75).Offering an insightful perspective on peace as a process through the long-term study of the lives of fifty former combatants, Söderström demonstrates how the process of coming home shapes their political commitment and identity. Combining detailed scholarship with interviews with former combatants, this volume serves as a powerful reminder of the legacies of war in the lives of former combatants.
Introduction1 Diverse wars and combatants2 Coming home and living peace?3 The politics of being a veteran4 Veteran networks throughout a lifetime5 Paths of mobilizationConclusionList of interviewsBibliographyIndex.
Description based on CIP data; resource not viewed.
eBooks on EBSCOhost
Keywords: Veterans -- Political activity; Vietnam War, 1961-1975 -- Veterans; Colombia -- Politics and government -- 1974-; Namibia -- Politics and government -- 1990-; Anciens combattants -- Activité politique; Guerre du Viêt-nam, 1961-1975 -- Anciens combattants; Namibie -- Politique et gouvernement -- 1990-; POLITICAL SCIENCE / Comparative Politics; Politics and government; Veterans; Veterans -- Political activity; Colombia; Namibia; Since 1961